2017
DOI: 10.1007/s00436-017-5395-0
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of Blumea eriantha essential oil and its components against six mosquito species, including Zika virus vectors: the promising potential of (4E,6Z)-allo-ocimene, carvotanacetone and dodecyl acetate

Abstract: The effective and environmentally sustainable control of mosquitoes is a challenge of essential importance. This is due to the fact that some invasive mosquitoes, with special reference to the Aedes genus, are particularly difficult to control, due to their high ecological plasticity. Moreover, the indiscriminate overuse of synthetic insecticides resulted in undesirable effects on human health and non-target organisms, as well as resistance development in targeted vectors. Here, the leaf essential oil (EO) ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…63 The karanjin (32) and karanjachromene (37) flavonoids were reported as strong inhibitors of AChE from mosquito larvae indicating it to be the presumable site of larvicidal action. The same results were observed for oleic (12), linoleic (38), linolenic (40), and palmitic (55) fatty acids. The fatty acids linoleic (38), linolenic (40), elaidic (51), arachidic (58), and behenic (62) presented to have an effect on the octopaminergic system.…”
Section: Mechanism Of Actionsupporting
confidence: 78%
“…63 The karanjin (32) and karanjachromene (37) flavonoids were reported as strong inhibitors of AChE from mosquito larvae indicating it to be the presumable site of larvicidal action. The same results were observed for oleic (12), linoleic (38), linolenic (40), and palmitic (55) fatty acids. The fatty acids linoleic (38), linolenic (40), elaidic (51), arachidic (58), and behenic (62) presented to have an effect on the octopaminergic system.…”
Section: Mechanism Of Actionsupporting
confidence: 78%
“…Further Benelli, G. et al [40] reported acute toxicity of montana essential oil and four other plant essential oils on C. quinquefasciatus larvae. Similarly, it has been reported that EO extracted from the leaves of B. eriantha showed high toxicity against third instar larvae of Anopheles, Aedes and Culex species, with LC 50 ranging from 41.61 to 61.33 lg/ml [41]. The susceptibility of the Asian tiger mosquito larvae to the Cannabis sativa and Humulus lupulus essential oils with LC 50 values of 302 and 331 lg/l respectively were observed [42].…”
Section: Larvicidal and Pupicidal Activity Of Aseo Pceo And Agnps Agmentioning
confidence: 70%
“…There are few alternate methods have been used preferentially such as botanicals, entomopathogenic fungus and aquatic predator etc. [3][4][5][6]. At present, nanotechnology have been widely used in all fields, especially, the silver nanoparticles are used in various field research, including pharmaceutical industries to develop a best anti-microbial drugs, agriculture, bio labeling, parasitology and pest management [7,8].…”
Section: Introductionmentioning
confidence: 99%